SWOT-Based Development Strategies for Micro, Small, and Medium Enterprises in Hutaraja Tinggi District - SIREGAR, FITRI HANDAYANI (Institut Agama Islam Persis Bandung, 2024)
Micro, Small, and Medium Enterprises (MSMEs) constitute the backbone of Indonesia’s economy—particularly in Hutaraja Tinggi District, Padang Lawas Regency—yet they face persistent constraints in access to capital, technology, market information, and skilled human resources. This study analyzes MSME development strategies using a qualitative SWOT approach to identify internal strengths and weaknesses and external opportunities and threats, and to formulate actionable strategies tailored to local conditions. Data were gathered through literature review, observation, and in-depth interviews with four business owners and one official from the District Office of Cooperatives, Industry, and Trade, with proportional sampling across enterprise types. Findings indicate key strengths in the availability of local raw materials, entrepreneurial drive, and distinctive products; principal weaknesses in limited financing, insufficient product innovation, and suboptimal marketing; opportunities in local government support, rising consumer purchasing power, and digital technology diffusion; and threats from intense competition, raw material price volatility, and shifting consumer preferences. The study recommends strategies focused on product quality upgrading, product diversification, the systematic use of digital marketing, and the strengthening of inter-organizational networks. Compared with prior studies that often isolate a single dimension (e.g., marketing or finance), this research offers a comprehensive, context-sensitive strategy set by integrating internal and external analyses within the SWOT framework, including attention to local socio-religious dynamics in a predominantly Muslim community.